Detection and quantification of 2H and 3R phases in commercial graphene-based materials - Seehra, Mohindar S.; Geddam, Usha K.; Schwegler-Berry, Diane; Stefaniak, Aleksandr B. (Carbon (New York), 2015)
Graphene-based material (GBM) samples acquired from commercial sources are investigated using X-ray diffraction (XRD). Of the 18 GBM samples investigated here, seven samples show XRD patterns with features characteristic of the graphite structure. The XRD patterns of the seven samples are analyzed showing the presence of both the ABA (2H) structure and the ABCA (3R) structure. After de-convoluting the (101) lines of the 2H and 3R structures, the areas under the peaks are used to determine the relative concentrations of the 2H and 3R phases present, typically yielding the ratio 60/40 for 2H/3R. The presence of the 3R structure is important since the 3R structure is a semiconductor with tunable band gap and it is less stable than the 2H structure. The number of layers determined from the analysis of the XRD data varies between 65 and 109 for different samples yielding thickness of the graphite sheets varying between 22 nm and 37 nm. Scanning electron microscopy and transmission electron microscopy of three representative samples confirms the sheet-like morphology and stacking of the graphene layers in the samples. Relevance of these results in connection with their potential applications and toxicology is briefly discussed.